ANALISIS PENGARUH BIJI KARET TERHADAP KUAT TEKAN BETON - Firdausa, Fadhila; Marpaung, Raja; Artini, Sri Rezki; Diba, Annadiyah Farah; Ria, Vicky Wisma; Iryani, Arista Widya (Jurnal Riset Rekayasa Sipil, 2020)
The development of technology construction has reached a period of caring for the environment. Many things been developed to support environmentally friendly construction. Itcan be started from the use of a mixture of natural ingredients into a mixture of construction materials. Concrete is a construction material that is often used in Indonesia, given its ease, price, and durabilityAlong with the development of the concrete periods has experienced many advances, one of which is in the drafting of a combined mix of making concrete, and to supporting environmentally friendly concrete, a mixture of natural materials are used as one of the making material of concrete.South Sumatra is one of the islands in Sumatra, which has an abundant plantation of rubber. The large number of rubber plantations makes rubber waste more and more, one of which is rubber seeds. Therefore it is necessary to treat rubber seed waste in order to reduce the amount of rubber seed waste and can be used to improve the economy of the surrounding community.  The rubber itself has many advantages in the industrial field. Utilization of rubber has been widely used, but no one has used rubber seeds as an aggregate substitution material in making a concrete without other chemicals. Therefore this research will discuss the rubber seed mixture as a substitute for coarse aggregate. The material used to make concrete is portland type I cement, coarse and fine aggregate from the Tanjung Raja area, and the rubber seeds used are from the Sembawa area. Coarse aggregate substitution using a mixture of rubber seeds  5%, 10%, 15%, and 20% were tested during the age of concrete of 7 days, 14 days, and 28 days.. The compressive strength of rubber seed substitution with a percentage of 5% shows the most significant compressive strength value of 19.33 Mpa. From the test results of this study it can be concluded that the greater the use of rubber seeds, the lower the compressive strength.